Can the EU’s Enhanced Co-operation Mechanism Provide Solutions to the “Single Undertaking” Problems of the WTO - Dragoș Negrescu (Romanian Journal of European Affairs, 2006)
The “Single Undertaking” is a feature making the WTO unique among multilateral organizations. Introduced at the end of the Uruguay Round, it seemed to promise a much smoother functioning of the multilateral trading system. Subsequent developments have not entirely validated these expectations. The problems engendered are remarkably similar to those faced by the process of deepening integration within the European Union, hence the modalities devised in the latter for overcoming them may offer a very useful source of inspiration.